Effect of volume of practice in children with probable Developmental Coordination Disorder - Leonardo Soares de Carvalho; Camila Sant Ana Crancianinov; Daniel Traina Gama; Cynthia Yukiko Hiraga (Universidade Federal de Santa Catarina, 2020)
Children with Developmental Coordination Disorder (DCD) demonstrate a slower and more gradual ability to acquire and learn motor skills with practice. One question then is whether a higher volume of practice for these children could match the performance of children with typical development (TD). The present study aims to examine the effects of a higher volume of practice by children with probable DCD (pDCD) in relation to a lower volume of practice by children with TD. The MABC-2 was used to identify the participants' level of motor difficulty and set the composition of the groups. Two active video games (Nintendo Wii) were used for the practice. Each group was composed of eight participants, paired up by gender and age, TD (M = 111.87 months; SD = 4.05) and pDCD (M = 115.87 months; SD = 4.96). The TD group participated in seven practice sessions and the pDCD group participated in eleven sessions. Results regarding performance on Wii console games showed significant improvement from the first day of practice to the last day in both groups (pDCD and TD). A higher volume of practice for children with pDCD compared to their TD peers helped to increase the performance of the former group. Therefore, the pDCD group achieved a performance similar to the TD group in both practiced games.